The potential of the Malabot Tumpe ethnobiology-containing e-module in realizing sustainable biodiversity conservation - Ghurrotul Bariroh; St. Syahirah; Riandi Riandi; Rini Solihat (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
Malabot Tumpe is local wisdom which has the meaning of realizing the 15th SDG goal in the conservation of maleo birds. Concepts such as ecosystem balance and biodiversity, which are reflected in Malabot Tumpe traditional practices, indicate the potential for Malabot Tumpe in integrating biology learning material, especially biodiversity material. The integration of values or knowledge from local wisdom containing ESD can be integrated into biology learning through e-modules. However, so far, there has been no research that specifically discusses the integration of Malabot Tumpe local wisdom, which contains sustainable conservation values, into biology learning. For this reason, the author aims to reveal the potential of e-modules containing Malabot Tumpe local wisdom as a form of implementing ESD in extracurricular biology learning activities in schools. The method used was a systematic literature review with a sample of 12 international and national articles. The result of this study is that there is potential for an E-module containing Malabot Tumpe local wisdom to not only help students achieve learning goals but also help sustainably preserve biodiversity. However, further research is needed to empirically measure the effectiveness of the Malabot Tumpe ethnobiology e-module and its impact on ESD to achieve sustainable biodiversity.Abstrak. Malabot Tumpe merupakan kearifan lokal yang mempunyai makna mewujudkan tujuan ke-15 SDGs dalam konservasi burung maleo. Konsep-konsep seperti keseimbangan ekosistem dan biodiversitas yang tercermin dalam praktik adat Malabot Tumpe mengindikasikan adanya potensi Malabot Tumpe dalam integrasi materi pembelajaran biologi khususnya materi keanekaragaman hayati. Integrasi nilai-nilai atau pengetahuan dari suatu kearifan lokal yang bermuatan ESD dapat diintegrasikan ke dalam pembelajaran biologi melalui e-modul. Namun sejauh ini belum ada penelitian yang secara khusus membahas integrasi kearifan lokal Malabot Tumpe yang mengandung nilai-nilai konservasi secara berkelanjutan, ke dalam pembelajaran biologi. Untuk itu penulis bertujuan ingin mengungkap bagaimana potensi e-modul bermuatan kearifan lokal Malabot Tumpe sebagai bentuk implementasi ESD dalam kegiatan intrakurikuler pembelajaran biologi di sekolah. Metode yang digunakan adalah tinjauan literatur sistematis dengan 12 sampel artikel internasional dan nasional. Hasil dari kajian ini adalah adanya potensi E-modul yang memuat kearifan lokal Malabot Tumpe tidak hanya membantu siswa mencapai tujuan pembelajaran tetapi sekaligus membantu pelestarian biodiversitas secara berkelanjutan. Namun dibutuhkan penelitian lebih lanjut untuk mengukur efektivitas e-modul bermuatan tetnobiologi Malabot Tumpe dan dampaknya terhadap ESD untuk mencapai biodiversitas yang berkelanjutan secara empiris.